Sistema especialista baseado em modelo ontológico para apoio ao projeto detalhado de produtos no contexto de máquinas agrícolas - Schmidt, Juliana (2017)
The large amount of available design information from different areas has become common in most organizations. Under these conditions, there are difficulties in sharing and reusing knowledge, especially by the fact that this knowledge is available within the company in different formats and locations. Due to this, design engineers often fail to use such information. To ensure a better use, it is important to organize and integrate the available knowledge in a collaborative manner. In this context, the Knowledge-based Engineering (KBE) approach can be associated. Through KBE concepts, the current study aims to develop an expert system based on an ontology model for assisting decision making, by storing and providing useful information in a timely manner. Such solution should meet the needs of its users (i.e. designers), as well as improve the quality of design activities along the Product Development Process (PDP). For this study, the following steps have been adopted: (a) delimitation of action scope (i.e. steps of PDP to be focused); (b) knowledge capture; (c) standardization; (d) knowledge structuring through ontologies; (e) building of queries; (f) evaluation of solution performance. The application of the present proposal aims to facilitate the access to information, significantly reduce the appearance of failures along the PDP, as well as allow acquired knowledge to be used in subsequent projects (e.g. lessons learned).